2013
DOI: 10.3748/wjg.v19.i11.1811
|View full text |Cite
|
Sign up to set email alerts
|

Value of α-fetoprotein in association with clinicopathological features of hepatocellular carcinoma

Abstract: HCC differentiation, size and vascular invasion have strong relationships with AFP, poor differentiation and HCC size ≥ 10 cm are independent predictors of elevated AFP. BCLC shows better relationship with AFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
82
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 39 publications
13
82
0
1
Order By: Relevance
“…Furthermore, AFP elevation in HCC was associated with macrovascular invasion in some studies [38,39] . In the present study, serum AFP levels were correlated with tumor size, which is consistent with the results of previous studies [5,35,36] . There was also a relationship between AFP levels and the tumor number, similar to the other studies [37,40] .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, AFP elevation in HCC was associated with macrovascular invasion in some studies [38,39] . In the present study, serum AFP levels were correlated with tumor size, which is consistent with the results of previous studies [5,35,36] . There was also a relationship between AFP levels and the tumor number, similar to the other studies [37,40] .…”
Section: Discussionsupporting
confidence: 82%
“…The relationship between serum AFP levels and tumor characteristics, such as tumor size, tumor number or macrovascular invasion, has been evaluated in many studies [31][32][33][34] . Liu et al [5] showed a relationship between AFP levels and tumor size, however, AFP concentrations…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although AFP is not elevated in all patients with HCC, a high serum AFP has been associated with advanced tumor stage, including greater tumor size, bilobar involvement, massive or diffuse-type tumor, poorer differentiation and PVT (18,19). The serum AFP level was found to be significantly higher in HCC patients with BCLC stage D compared to stage A and B (18) and was also associated with prognosis. In addition, the AFP level has been considered as an important predictor of postoperative HCC recurrence and metastasis (20,21).…”
Section: Discussionmentioning
confidence: 81%